Ceramic tile adhesive based on copper tailing sand as well as preparation method and application of ceramic tile adhesive

By adjusting the ratio of cement, copper tailings sand and resin powder, tiles with high copper tailings sand content are prepared, which solves the problem of loosening and mechanical properties of ceramic tiles glue caused by high copper tailings sand addition, and achieves the effect of increasing the recycling and utilization of copper tailings sand and reducing the cement addition.

CN119797830APending Publication Date: 2025-04-11TONGLING NONFERROUS METALS GRP TONGGUAN CONSTR & INSTALLATION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411714581.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The higher the amount of copper tailings sand added in existing ceramic tile glue, the looser the prepared ceramic tile glue, and the mechanical properties decline in the later stage, resulting in a lower content of copper tailings sand and cannot be used as the main raw material.

Method used

By adjusting the weight ratio of cement, copper tailings sand and resin powder, a ceramic tile glue with high copper tailings sand content is prepared, including 100 parts of cement, 115 to 145 parts of copper tailings sand, 18 to 25 parts of resin powder, 0.5 to 1.2 parts of water retention agent and 0.5 to 1.5 parts of premature strength agent.

Benefits of technology

While maintaining the performance of tiles to meet the standards, the recycling and utilization of copper tailings sand is increased, the addition of cement is reduced, the cost is reduced, and the adhesion and mechanical properties of tiles are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156613420000071
    Figure BDA0005156613420000071
  • Figure BDA0005156613420000081
    Figure BDA0005156613420000081
Patent Text Reader

Abstract

The invention discloses ceramic tile glue based on copper tailing sand, a preparation method and application. Relates to the technical field of copper tailing sand recycling, in particular to a ceramic tile adhesive based on copper tailing sand, which is prepared from the following components in parts by weight: 100 parts of cement; 115 to 145 parts of copper tailing sand; 18 to 25 parts of resin powder; 0.5 to 1.2 parts of a water-retaining agent; and 0.5-1.5 parts of an early strength agent. The copper tailing sand is crushed and dried; mixing the copper tailing sand, the resin powder, the water-retaining agent and the early strength agent, adding the cement, and uniformly mixing to obtain the ceramic tile adhesive based on the copper tailing sand. The tile adhesive is applied to the fields of buildings and construction. The copper tailing sand is used as a main raw material for preparing the ceramic tile adhesive, the weight ratio of the cement is reduced, and under the condition that the performance of the ceramic tile adhesive reaches the standard, the recycling amount of the copper tailing sand is increased, the addition amount of the cement is reduced, and the cost is reduced; the ceramic tile adhesive prepared by the invention is relatively good in adhesive force, and various mechanical properties of the ceramic tile adhesive can be kept to reach the standard under the condition that relatively high content of copper tailing sand is added.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of copper tailings sand recycling and utilization, and in particular to a ceramic tile adhesive based on copper tailings sand, a preparation method and an application thereof. Background Art

[0002] Tile adhesive is a new type of decoration material specially used for bonding ceramic tiles. In the original tile laying process, cement mortar is generally used as a bonding agent between the base and the tile. Modern people have higher and higher requirements for the quality of life, and have also put forward higher requirements for decorative materials, constantly emphasizing aesthetics and environmental protection. Tiles are also increasingly developing towards large-size, low-permeability, wear-resistant, good anti-fouling, and easy-to-clean vitrified tiles.

[0003] The density of this type of tile is getting higher and higher, the back is becoming smoother, the pores are drastically reduced, and the water absorption rate is getting worse, which brings great difficulty to the pasting of tiles. The traditional cement paste pasting method can no longer meet the needs of modern tile paving.

[0004] Therefore, it is necessary to use tile adhesive with better adhesive properties. Copper tailings refer to the solid waste discharged from mines that mainly mine copper resources after the useful components in the ore are separated through mineral processing. The mineral aggregates that account for more than 60% of tile adhesives are generally machine-made sand and river sand, which are very similar in composition to copper tailings sand. The silicon and calcium content of copper tailings sand is very suitable for replacing mineral aggregates to prepare tile adhesives, and the proportion of mineral aggregates is relatively large. The use of copper tailings for substitution is conducive to the large-scale disposal of copper tailings sand.

[0005] However, the higher the amount of copper tailings added to the tile adhesive, the looser the prepared tile adhesive will be, and the later mechanical properties will decrease. Therefore, the content of copper tailings in current tile adhesives is relatively low and cannot be used as the first main raw material. Therefore, it is necessary to develop a formula to increase the weight proportion of copper tailings in the tile adhesive, and the performance of the tile adhesive will not decrease or will decrease slightly. Summary of the invention

[0006] In order to solve at least one of the above technical problems, a tile adhesive with high copper tailings content and excellent performance is developed. The present application provides a tile adhesive based on copper tailings, a preparation method and an application.

[0007] On the one hand, the present application provides a copper tailings sand-based tile adhesive, which is prepared by the following components in parts by weight:

[0008] 100 parts of cement;

[0009] 115-145 parts of copper tailings;

[0010] 18-25 parts of resin powder;

[0011] Water-retaining agent 0.5-1.2 parts;

[0012] 0.5 to 1.5 parts of early strength agent.

[0013] Optionally, the weight ratio of the cement, copper tailings sand and resin powder is 100:125-135:22-25.

[0014] Optionally, the cement is early strength silicate cement with a strength grade of 42.5R and an alkali content controlled at ≤1%.

[0015] Optionally, the copper tailings sand has a particle size not exceeding 0.3 mm and a moisture content not exceeding 1%.

[0016] Optionally, the resin powder is made of polyurethane.

[0017] Optionally, the water retaining agent is carboxymethyl cellulose.

[0018] Optionally, the early strength agent is carbonate.

[0019] In a second aspect, the present application provides a method for preparing the above-mentioned copper tailings sand-based tile adhesive, comprising the following steps:

[0020] S1. Copper tailings sand treatment

[0021] Crushing the copper tailings and drying them to a moisture content of less than 1%;

[0022] S2. Preparation of tile adhesive

[0023] The copper tailings sand treated in S1, resin powder, water retaining agent and early strength agent are mixed, and then cement is added and mixed evenly to obtain copper tailings sand-based tile adhesive.

[0024] In a third aspect, the present application provides the application of the above-mentioned copper tailings sand-based tile adhesive in the field of building and construction.

[0025] In summary, the present invention includes at least one of the following beneficial technical effects:

[0026] 1. This application uses copper tailings as the main raw material for preparing tile adhesive, reduces the weight proportion of cement, and increases the recycling amount of copper tailings, reduces the amount of cement added, and reduces costs when the tile adhesive performance meets the standards;

[0027] 2. The present application controls the weight ratio of copper tailings, cement and resin powder so that the prepared tile adhesive has good adhesion, and when a higher content of copper tailings is added, the mechanical properties of the tile adhesive can be kept up to standard;

[0028] 3. This application promotes early hardening while maintaining good long-term performance by adding a suitable ratio of water-retaining agent and early strength agent. DETAILED DESCRIPTION

[0029] The present application is further described in detail below with reference to the embodiments.

[0030] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products.

[0031] The cement in the following embodiments of the present application is early-strength Portland cement with a strength grade of 42.5R and an alkali content controlled at ≤1%.

[0032] The copper tailings sand in the following examples of the present application has a particle size of no more than 0.3 mm and a moisture content of no more than 1%.

[0033] The resin powder in the following embodiments of the present application is polyurethane.

[0034] The water-retaining agent in the following examples of the present application is exemplarily carboxymethyl cellulose.

[0035] The early strength agent in the following examples of the present application is sodium carbonate. Specific embodiments

[0037] Example 1

[0038] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0039] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0040] 115 kg of the treated copper tailings, 18 kg of polyurethane powder, 1.2 kg of carboxymethyl cellulose and 0.5 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0041] Example 2

[0042] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0043] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0044] 120 kg of the treated copper tailings, 20 kg of polyurethane powder, 1.0 kg of carboxymethyl cellulose and 1 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0045] Example 3

[0046] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0047] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0048] 125 kg of the treated copper tailings, 22 kg of polyurethane powder, 0.8 kg of carboxymethyl cellulose and 1.5 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0049] Example 4

[0050] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0051] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0052] 130 kg of the treated copper tailings, 25 kg of polyurethane powder, 0.5 kg of carboxymethyl cellulose and 1 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0053] Example 5

[0054] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0055] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0056] 135 kg of the treated copper tailings, 22 kg of polyurethane powder, 0.8 kg of carboxymethyl cellulose and 0.5 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0057] Example 6

[0058] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0059] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0060] 140 kg of the treated copper tailings, 20 kg of polyurethane powder, 1.0 kg of carboxymethyl cellulose and 1 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0061] Example 7

[0062] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0063] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0064] 145 kg of the treated copper tailings, 18 kg of polyurethane powder, 1.2 kg of carboxymethyl cellulose and 1.5 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0065] Comparative Example 1

[0066] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0067] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0068] 100 kg of the treated copper tailings, 18 kg of polyurethane powder, 1.2 kg of carboxymethyl cellulose and 0.5 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0069] Comparative Example 2

[0070] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0071] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0072] 105 kg of the treated copper tailings, 20 kg of polyurethane powder, 0.8 kg of carboxymethyl cellulose and 1 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0073] Comparative Example 3

[0074] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0075] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0076] 110 kg of the treated copper tailings, 25 kg of polyurethane powder, 0.5 kg of carboxymethyl cellulose and 1.5 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0077] Comparative Example 4

[0078] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0079] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0080] 150 kg of the treated copper tailings, 25 kg of polyurethane powder, 0.5 kg of carboxymethyl cellulose and 1.5 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0081] Comparative Example 5

[0082] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0083] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0084] 155 kg of the treated copper tailings, 20 kg of polyurethane powder, 0.8 kg of carboxymethyl cellulose and 1 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0085] Comparative Example 6

[0086] The preparation method of the tile adhesive based on copper tailings sand comprises the following steps:

[0087] Crushing the copper tailings to less than 3mm and drying them to a moisture content of less than 1%;

[0088] 160 kg of the treated copper tailings, 18 kg of polyurethane powder, 1.2 kg of carboxymethyl cellulose and 0.5 kg of sodium carbonate were mixed, and then 100 kg of cement was added and mixed evenly to obtain a copper tailings-based tile adhesive.

[0089] The copper tailings sand-based tile adhesives prepared in Examples 1 to 7 and Comparative Examples 1 to 6 were mixed with water at a weight ratio of 4:1, and the properties were tested after curing to the specified age according to JC / T 547-2017 standard. The test results are shown in Table 1.

[0090] Table 1

[0091]

[0092]

[0093] It can be seen from Examples 1 to 7, Comparative Examples 1 to 6 and Table 1 that the original tensile adhesive strength of the copper tailings sand-based tile adhesive prepared by the technical solution of the present application can reach more than 1 MPa, the tensile adhesive strength after heat aging can reach more than 0.9 MPa, and the tensile adhesive strength after immersion in water can reach more than 0.6 MPa, which can meet the requirements of ordinary cement-based adhesives in the JC / T 547-2017 standard.

[0094] Moreover, for the copper tailings sand-based tile adhesive prepared by the technical solution of the present application, when the weight ratio of cement, copper tailings sand and resin powder is in the range of 100:125-135:22-25, the tile adhesives corresponding to Examples 3-5 have an original tensile adhesive strength of more than 1 MPa, a tensile adhesive strength after heat aging of more than 1 MPa, and a tensile adhesive strength after immersion in water of more than 1 MPa, which can meet the requirements of the reinforced cement-based adhesive in the JC / T 547-2017 standard.

[0095] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A tile adhesive based on copper tailings sand, characterized in that: The method is prepared by comprising the following components in parts by weight: 100 parts of cement; 115-145 parts of copper tailings; 18-25 parts of resin powder; Water-retaining agent 0.5-1.2 parts; 0.5 to 1.5 parts of early strength agent.

2. The copper tailings sand-based tile adhesive according to claim 1, characterized in that: The weight ratio of the cement, copper tailings sand and resin powder is 100:125-135:22-25.

3. The copper tailings sand-based tile adhesive according to claim 1, characterized in that: The cement is early strength silicate cement with a strength grade of 42.5R and an alkali content controlled at ≤1%.

4. The copper tailings sand based tile adhesive according to claim 1, characterized in that: The copper tailings sand has a particle size of no more than 0.3 mm and a moisture content of no more than 1%.

5. The copper tailings sand based tile adhesive according to claim 1, characterized in that: The resin powder is polyurethane.

6. The copper tailings sand based tile adhesive according to claim 1, characterized in that: The water retaining agent is carboxymethyl cellulose.

7. The copper tailings sand-based tile adhesive according to claim 1, characterized in that: The early strength agent is carbonate.

8. A method for preparing a ceramic tile adhesive based on copper tailings sand according to claim 1, characterized in that: The following steps are involved: S1. Copper tailings sand treatment Crushing the copper tailings and drying them to a moisture content of less than 1%; S2. Preparation of tile adhesive The copper tailings sand treated in S1, resin powder, water retaining agent and early strength agent are mixed, and then cement is added and mixed evenly to obtain copper tailings sand-based tile adhesive.

9. Use of the copper tailings sand based tile adhesive according to claim 1 in the field of building and construction.